The Electron Neutrino Mass: Between Experimental Measurements and Theoretical Calculations (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Basic Sciences Series, 2026)
The electron neutrino, a fundamental particle in the Standard Model of elementary particle physics, is a very small particle, with no electric charge, was long thought to be massless. It is known for its elusive nature and weak interactions with other particles (its extremely low effective cross-section σ), making its detection and study challenging. Recent experimental developments have shed light on its properties, such as its oscillatory behavior and its participation in nuclear interactions. Understanding the electron neutrino is crucial for unlocking the secrets of the fundamental particles and forces of the universe. In this work, the mass of the electron neutrino was calculated theoretically, based on the experimental values ​​of the Triple Correlation Coefficient in nuclear beta decay, extracted from the tritium beta decay probability relation taken at the end of the spectrum, which includes the asymmetry coefficient , and the Triple Correlation Coefficient , which implicitly contain the mass of the electron neutrino. We then used the Mathematica software to obtain the relevant electron neutrino mass values ​​ and compared them with other theoretical methods (the method of  Takaaki  Kajita and Arthur McDonald, who based their calculations on the Higgs field and the mass of the Majorana neutrino) and with the latest experimental values, and in particular the values ​​measured in the KATRIN experiment.
Keywords: electron neutrino, beta decay , asymmetry coefficient, triple correlation coefficient.